2016
DOI: 10.1155/2016/5281823
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Immune Stimulation Analysis of Primary Human B Cells and B Cell Lines

Abstract: B cell specific immunomodulatory drugs still remain an unmet medical need. Utilisation of validated simplified in vitro models would allow readily obtaining new insights in the complexity of B cell regulation. For this purpose we investigated which human B lymphocyte stimulation assays may be ideally suited to investigate new B lymphocyte immunosuppressants. Primary polyclonal human B cells underwent in vitro stimulation and their proliferation, production of immunoglobulins (Igs) and of cytokines, and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 34 publications
5
59
0
Order By: Relevance
“…Clearly, this rather broad stimulation protocol results in activation of several signaling pathways, including the JAK/STAT pathway for cytokines, TRAF/MAPK for CD40 ligation and MyD88/IRAK for the TLR9 agonist. In agreement with Van Belle et al [38], we found that in vitro stimulation through TLR9 was a main driver of IgG secretion in these assays (Figure 1). In summary, although this stimulation protocol represents a model system that may not reflect all fysiological features of B-cell maturation, it captures broad aspects of B-cell biology and provides a highly relevant starting point for further studies.…”
Section: Discussionsupporting
confidence: 93%
“…Clearly, this rather broad stimulation protocol results in activation of several signaling pathways, including the JAK/STAT pathway for cytokines, TRAF/MAPK for CD40 ligation and MyD88/IRAK for the TLR9 agonist. In agreement with Van Belle et al [38], we found that in vitro stimulation through TLR9 was a main driver of IgG secretion in these assays (Figure 1). In summary, although this stimulation protocol represents a model system that may not reflect all fysiological features of B-cell maturation, it captures broad aspects of B-cell biology and provides a highly relevant starting point for further studies.…”
Section: Discussionsupporting
confidence: 93%
“…B cells can be activated by a variety of stimuli to acquire immunostimulatory capacity, including B-cell receptor (BCR) binding to antigen and toll-like receptor-mediated signals. However, signals transmitted via CD40 have consistently been found to be the most potent inducer of many features of potent APCs [2]. Several strategies have been investigated to exploit CD40-CD40L interaction for the generation of antigen-presenting B cells (summarized in Table 1 for human B cells ) [reviewed in 21].…”
Section: Generation Of Antigen-presenting B Cellsmentioning
confidence: 99%
“…Soon after CD40 and its ligand CD40L (also named CD154) were first described, it became clear that CD40L/CD40 signaling was among the most potent stimuli for the activation of B cells [2, 3]. Classically, CD40L is expressed on activated CD4+ T cells and, thus, is essential for a thymus-dependent B-cell response and for the development of a humoral and cellular immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is an unmet need for new B cell drugs that aim for a modulation of B cell's activation status. Recently, we described the oligodeoxynucleotide (ODN) 2006-stimulated Namalwa cell line as a relevant, homogeneous, and stable B cell activation model by which new targets and inhibitors of the B cell activation processes can be identified through flow cytometric analysis of the expression of activation and costimulatory cell surface markers [ 1 ]. In search of innovative B cell immunomodulating agents, this assay was chosen to screen a library of chemical agents for inhibitory effects on activated human B cells.…”
Section: Introductionmentioning
confidence: 99%